Effect of Chelate Ring Size of Binuclear Copper(II) Complexes on Catecholase Activity and DNA Cleavage. Issue 18 (7th April 2021) - Homrich, Alana M.; Farias, Giliandro; Amorim, Suélen M.; Xavier, Fernando R.; Gariani, Rogério A.; Neves, Ademir; Terenzi, Hernán; Peralta, Rosely A.
Abstract: Catecholase activity of dicopper(II) complexes containing different numbers of chelate members in the pyridine groups of the ligand was studied to identify a functional model for copper enzyme catechol oxidase. Complexes [Cu II (μ‐OH)Cu II (L1 )](ClO4 ) (1 ), [Cu II (μ‐OH)Cu II (L2 )](ClO4 ) (2 ), and [Cu II (μ‐OH)Cu II (L3 )](ClO4 ) (3 ) were synthesized and characterized by elemental analysis, FTIR, UV–Vis spectroscopy, mass spectrometry, and electrochemistry. Their catalytic activity in the oxidation of 3, 5‐di‐ tert‐ butylcatechol was determined. Changing the number of members of the chelate rings altered the catalytic activity. Complex 2 showed the highest catalytic activity due to a high turnover rate, with efficiency of 3.40±0.61. Mechanistic investigations indicate that the catalytic reaction occurs through the reduction of Cu(II) to Cu(I) with formation of hydrogen peroxide. The spectroscopic and catecholase activity were further rationalized through DFT and TD‐DFT calculations. Interestingly, all three complexes also showed DNA binding properties, which were also corroborated via molecular docking studies. Abstract : Three copper binuclear complexes that differ by the number of chelate member rings of the ligand were synthesized and characterized. The effect of these modifications on the enzyme mimicking (catecholase and DNAse) was evaluated, revealing that changes in the soft side contributed positively to the activity.